Analysis of heart rate variability in pre-eclamptic pregnancy: a study employing frequency domain analysis - Navi Khan, Gul Ar; Ishrat, Nazia; ., Zulquarnain (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Preeclampsia is a disorder characterized by development of hypertension to the extent of 140/90 mmHg or more with proteinuria after 20th weeks of pregnancy in a previously normotensive and non proteinuric woman. Physiologically blood pressure is controlled by Autonomic Nervous System (ANS) so study of ANS during pregnancy plays a significant role to extract some vital information which may be helpful to deal with Pregnancy Induced Hypertension (PIH) or preeclampsia. The autonomic nervous system and changes in ANS during different pathophysiological conditions could be evaluated with heart rate variability analysis test. The modification in the autonomic control occurs during pregnancy and its evaluation through Heart Rate Variability (HRV) analysis is very informative technique now a day but studied little thus the main objective of our project is to compare the maternal HRV changes between normal pregnancy and pre-eclamptic pregnancy. Methods: 48 subjects (33 of normotensive pregnant women i.e., control group and 15 pre-eclamptic pregnant women i.e, study group) of more than 20 weeks pregnancy were recruited from the outpatients, antenatal unit and wards of obstetrics & gynaecology department of JNMC, AMU, Aligarh. Physical examination was done and anthropometric measurement like height & weight were taken. BMI was calculated as per Quetlet’s index. Urine test was conducted to every pregnant woman for urine albumin and we designated the pregnant women as pre-eclamptic women on the basis of definition. The subject was advised to take complete bed rest in supine position for 15 minutes in a cool and calm environment. The recording of short term HRV was done according to recommendation of the task force on HRV. The data was transferred from Medicaid machine to window based computer with HRV analysis software. Frequency domain analysis of HRV was taken for further statistical analysis. Results: There was no significant difference of body mass index was present between them but BMI of pre-eclamptic pregnant women was higher than normotensive pregnant women and it come under obese category (>25). Systolic blood pressure and Mean arterial pressure of study group was significantly higher than control group while diastolic pressure was not significantly higher. All the component of spectral analysis i.e., peak frequency (in Hz) and peak frequency (in normalized unit) of pre-eclamptic pregnant women was significantly higher than normotensive pregnant women while in peak power (%) Low Frequency (LF) & ratio between LF/HF of peak power was significantly higher than normotensive pregnant women. Others component of peak power (in %) parameters like VLF & HF between normotensive and pre-eclamptic women’s were non-significant. Conclusions: The present study clearly indicates that the contribution of anthropometric parameters to the blood pressure changes in pregnancy is negligible between the two groups. Frequency domain analysis showed sympathetic dominance and vagal withdrawal in pre-eclamptic pregnant women. Analysis of sympathetic exaggeration helps us for early detection & treatment of pre-eclampsia. Study on large sample size and estimation of placental factors (cytokines & reactive oxygen species) could have been better explained the pathophysiology of preeclampsia.